2015
DOI: 10.1007/s13205-015-0282-9
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of waste lubricants by a newly isolated Ochrobactrum sp. C1

Abstract: A potential degrader of paraffinic and aromatic hydrocarbons was isolated from oil-contaminated soil from steel plant effluent area in Burnpur, India. The strain was investigated for degradation of waste lubricants (waste engine oil and waste transformer oil) that often contain EPA (Environmental Protection Agency, USA) classified priority pollutants and was identified as Ochrobactrum sp. C1 by 16S rRNA gene sequencing. The strain C1 was found to tolerate unusually high waste lubricant concentration along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 41 publications
1
23
0
2
Order By: Relevance
“…For the obligate aerobic genus Ochrobactrum , some isolated Ochrobactrum sp. from wastewater treatment plant, petroleum refinery wastewater or petroleum‐contaminated soil have been reported . The exoelectrogenic bacterium Ochrobactrum anthropi YZ‐1 has been isolated by Bruce E. Logan, where the maximum power density was 89 mW m −2 for YZ‐1 strain .…”
Section: Resultsmentioning
confidence: 99%
“…For the obligate aerobic genus Ochrobactrum , some isolated Ochrobactrum sp. from wastewater treatment plant, petroleum refinery wastewater or petroleum‐contaminated soil have been reported . The exoelectrogenic bacterium Ochrobactrum anthropi YZ‐1 has been isolated by Bruce E. Logan, where the maximum power density was 89 mW m −2 for YZ‐1 strain .…”
Section: Resultsmentioning
confidence: 99%
“…Several strains of hydrocarbon-oxidizing bacteria can be found within the Ochrobactrum genus, but only a few ones were shown to exhibit diversified biochemical capabilities. Bhattacharya et al (2015) isolated Ochrobactrum sp. C1 which could grow in the presence of a wide range of compounds (nC 12 -nC 28 , phenanthrene and anthracene) and waste lubricants.…”
Section: Bacteria Able To Metabolize Both N-alkanes and Aromatic Hydrmentioning
confidence: 99%
“…Another approach that has been applied is based on biodegradation of multicomponent mixtures containing both aliphatic and aromatic compounds, such as coal tar (Pasternak et al 2011), fuel oil (Vila and Grifoll 2009), crude oil (Mittal and Singh 2009), lubricant wastes (Bhattacharya et al 2015) or petroleum sludge (Bezza et al 2015). In these cases, the GC-MS technique was found to be especially applicable by facilitating determination of individual compounds in the analyzed complex mixtures (Whyte et al 1997;Pasternak et al 2011) or accumulated metabolites (Vila et al 2001;Vila and Grifoll 2009).…”
Section: Evaluation Of Metabolic Preferences Towards Both N-alkanes Amentioning
confidence: 99%
“…Su et al, 18 demonstrated the motor-oil-degrading potential of an indigenous Pseudomonas aeruginosa SU-1 bacterial strain was found to have the capacity to degrade engine oil effectively. Bhattacharya et al, 14 reported that a newly isolated Ochrobactrum sp. C1 could grow with waste lubricants.…”
Section: Biodegradation Efficiency Of Bioreactormentioning
confidence: 99%